MEMBANGUN AKUNTABILITAS KINERJA INSTANSI PEMERINTAH MELALUI KOMPETENSI, KEJELASAN SASARAN ANGGARAN, DAN SISTEM PELAPORAN: BUILDING GOVERNMENT PERFORMANCE ACCOUNTABILITY THROUGH COMPETENCE, BUDGET GOAL CLARITY, AND REPORTING SYSTEM - Warni, Anggi Risma; Darlis, Edfan; Al Azhar A (Universitas Riau, 2025)
This study aims to analyze the influence of human resource competence, budget goal clarity, and reporting systems on government agency performance accountability. The research was conducted within Regional Apparatus Organizations (OPD) in Rokan Hulu Regency. A quantitative approach was employed using surveys and questionnaires distributed to 225 respondents consisting of financial officers and relevant staff from 45 OPD. The findings reveal that human resource competence, budget goal clarity, and reporting systems each have a significant positive impact on the performance accountability of government agencies. These results highlight the importance of strengthening staff competence, ensuring clear and measurable budget targets, and developing transparent reporting mechanisms to enhance accountability practices. The study contributes theoretically by providing empirical evidence that integrates resource-based and system theories in the context of local government performance. Practically, the findings offer insights for policymakers and regional leaders to design more effective capacity-building programs, budget planning, and performance reporting systems to support sustainable improvements in public accountability.